Pulmonary Hypertension in Pregnancy: Critical Care Management - Adel M. Bassily-Marcus; Carol Yuan; John Oropello; Anthony Manasia; Roopa Kohli-Seth; Ernest Benjamin (Pulmonary Medicine)
Pulmonary hypertension is common in critical care settings and in presence of right ventricular failure is challenging to manage. Pulmonary hypertension in pregnant patients carries a high mortality rates between 30–56%. In the past decade, new treatments for pulmonary hypertension have emerged. Their application in pregnant women with pulmonary hypertension may hold promise in reducing morbidity and mortality. Signs and symptoms of pulmonary hypertension are nonspecific in pregnant women. Imaging workup may have undesirable radiation exposure. Pulmonary artery catheter remains the gold standard for diagnosing pulmonary hypertension, although its use in the intensive care unit for other conditions has slowly fallen out of favor. Goal-directed bedside echocardiogram and lung ultrasonography provide attractive alternatives. Basic principles of managing pulmonary hypertension with right ventricular failure are maintaining right ventricular function and reducing pulmonary vascular resistance. Fluid resuscitation and various vasopressors are used with caution. Pulmonary-hypertension-targeted therapies have been utilized in pregnant women with understanding of their safety profile. Mainstay therapy for pulmonary embolism is anticoagulation, and the treatment for amniotic fluid embolism remains supportive care. Multidisciplinary team approach is crucial to achieving successful outcomes in these difficult cases.